The prevalence of expiratory flow limitation in youth elite male cyclists - Cox, K. R.; Smith, J. R.; Luden, N. D.; Saunders, M. J.; Kurti, S. P. (Medicine & Science in Sports & Exercise, 2020)
The present investigation tested the hypotheses that there would be greater prevalence of expiratory flow limitation (EFL) in endurance-trained (ET) youth cyclists compared with a recreationally active control (CON) group. METHODS: Twelve ET youth male cyclists (16.3 ± 1.0 yr (13-18 yr), 176.5 ± 6.2 cm, 64.2 ± 5.9 kg) and 12 CON subjects (17.6 ± 2.2 yr (13-18 yr), 177.9 ± 7.1 cm, 74.8 ± 11.2 kg) completed an incremental exercise test to determine peak oxygen consumption (V.O2peak) on a cycle ergometer. Maximal flow volume loops (MFVL), forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1/FVC, forced expiratory flow between 25% and 75% of FVC, and peak expiratory flow were assessed before and after exercise, with inspiratory capacity maneuvers and dyspnea ratings measured in the last 20 s of each stage. EFL was quantified as the percentage of the expiratory tidal volume that overlapped with the maximal flow volume loop. RESULTS V.O2peak, dyspnea ratings at peak, and ventilation were higher in the ET compared with CON group (P < 0.05). The ET group experienced greater EFL prevalence at V.O2peak, with 11 of 12 subjects exhibiting EFL compared with 5 of 12 subjects in the CON group (P = 0.014). When matched for absolute ventilation of 20, 40, 60, 80, and 100 L·min-1, there were no differences in EFL severity between the ET and CON groups (P = 0.473). CONCLUSIONS: Elite youth male cyclists have a greater prevalence of EFL at maximal exercise than do CON subjects who are similar in age, height, and lung size. Future research should determine whether EFL in youth ET male cyclists may limit their exercise performance.